2013
DOI: 10.1126/science.1225411
|View full text |Cite
|
Sign up to set email alerts
|

Recent Changes in the Ventilation of the Southern Oceans

Abstract: Surface westerly winds in the Southern Hemisphere have intensified over the past few decades, primarily in response to the formation of the Antarctic ozone hole, and there is intense debate on the impact of this on the ocean's circulation and uptake and redistribution of atmospheric gases. We used measurements of chlorofluorocarbon-12 (CFC-12) made in the southern oceans in the early 1990s and mid-to late 2000s to examine changes in ocean ventilation. Our analysis of the CFC-12 data reveals a decrease in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
175
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(204 citation statements)
references
References 30 publications
27
175
2
Order By: Relevance
“…And although it is impossible to directly measure the strength of the upwelling, changes in the distribution of chlorofluorocarbons in the ocean suggest that upwelling may have increased in response to the wind increase. 9 In addition to those changes in the upper ocean, Antarctic bottom water-the deepest water mass in the Southern Ocean-has also warmed rapidly in recent decades. 10 It's not clear what's causing the abyssal warming, which is strongest in the south and concentrated along the northward pathways.…”
Section: Rapid Heat Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…And although it is impossible to directly measure the strength of the upwelling, changes in the distribution of chlorofluorocarbons in the ocean suggest that upwelling may have increased in response to the wind increase. 9 In addition to those changes in the upper ocean, Antarctic bottom water-the deepest water mass in the Southern Ocean-has also warmed rapidly in recent decades. 10 It's not clear what's causing the abyssal warming, which is strongest in the south and concentrated along the northward pathways.…”
Section: Rapid Heat Uptakementioning
confidence: 99%
“…9,15 First, the delivery of more carbon-rich water to the surface increases the degassing of CO 2 . Second, the greater nutrient delivery and changed surfacewater properties alter the efficiency of the biological pump.…”
Section: Southern Oceanmentioning
confidence: 99%
“…Several authors have indicated how wind oscillations may be altered as anthropogenic gases heat the earth's troposphere, or deplete ozone, and as atmospheric water vapor concentrations change [94][95][96][97][98]. For example, as the greenhouse gases CO 2 and CH 4 accumulate in the troposphere and trap heat, the stratosphere is cooled, intensifying the westerly winds at both poles [94].…”
Section: The Future: Anthropogenic Climate Changementioning
confidence: 99%
“…For example, as the greenhouse gases CO 2 and CH 4 accumulate in the troposphere and trap heat, the stratosphere is cooled, intensifying the westerly winds at both poles [94]. Global warming due to greenhouse gases apparently intensifies the positive phase of the cycle [95][96][97][98]. The recent zonal phase, of the westerly winds in the northern hemisphere from the 1970s to the 1990s, was the strongest NAO oscillation in the recorded record [17].…”
Section: The Future: Anthropogenic Climate Changementioning
confidence: 99%
“…Likewise in the Southern Hemisphere, the ozone hole does not influence only the levels of incoming ultraviolet radiation. Together with greenhouse warming, it also alters the southern westerly wind systems 7 , summer climate 8 and the Southern Ocean's ability to take up trace gases from the atmosphere 9 .…”
mentioning
confidence: 99%